Penggunaan Instrumen Sosiometri dalam Layanan Bimbingan dan Konseling - Wahyuni, Siti (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2019)
Sociometry is a method for collecting data about the patterns and structure of relationships between individuals in a group. This method is based on the idea that groups have a structure consisting of complex interpersonal relationships. The position of each individual and the relationships that occur in the group structure can be measured quantitatively and qualitatively. The results of sociometric processing will be an illustration of the number of scores obtained by each person, the relationship pattern, the intensity of the relationship, and the position of the students in the group.Keywords: SociometryAbstrakSosiometri adalah suatu metode untuk mengumpulkan data tentang pola dan struktur hubungan antara individu-individu dalam kelompok. Metode ini didasarkan pada pemikiran bahwa kelompok mempunyai struktur yang terdiri dari hubungan-hubungan interpersonal yang kompleks. Posisi setiap individu dan hubungan-hubungan yang terjadi dalam struktur kelompoknya dapat diukur secara kuantitatif dan kualitatif. Hasil pengolahan sosiometri akan diperoleh gambaran jumlah skor yang diperoleh setiap orang, pola hubungan, intensitas hubungan, dan posisi peserta didik dalam kelompoknya.Kata Kunci : Sosiometri